Mooving Smart Mobility & Energy Pvt. Ltd.: Dwindling Customer Base - Geetanjali Sahi, Khushi Garg (Journal of Informatics Education and Research, 2023)
On the evening of 2nd May 2023, Sanchit Gupta, the business lead of Mooving Smart Mobility & Energy Pvt. Ltd. (Mooving) was reviewing the list of e-rickshaw drivers enrolled with his organization and was surprised to see e-richshaw drivers dropping out of Mooving’s battery leasing and swapping services. The enrollment figures which were high during the last quarter of 2022 had now plateaued. Although the popularity and market share of e-rickshaws was soaring nationally and globally at unprecedented rates, primarily owing to their economic, ergonomic, and environmental advantages (Invest India 2022), the numbers before him were conveying a different picture altogether.